CONTROVERSIAL ISSUES TO IMPROVE STUDENTS' MATHEMATICAL REASONING AND CRITICAL THINKING: A SYSTEMATIC LITERATURE REVIEW: Bali, Indonesia - Ida Ayu Putu Mahayani; I Gusti Ngurah Pujawan; I Putu Pasek Suryawan (Jurnal Math-UMB.EDU, 2026)
The rapid development of education in the digital era and the Industrial Revolution 4.0 requires students to master higher-order thinking skills such as reasoning and critical thinking, which are essential for solving complex mathematical problems. This study aims to analyze and describe the role of controversial issues in developing students’ mathematical reasoning and critical thinking skills. The research employed a Systematic Literature Review (SLR) with a descriptive qualitative approach. Articles were selected through a systematic search of Google Scholar, ResearchGate, Scopus, ERIC, and Web of Science using keywords related to controversial issues, mathematical reasoning, and critical thinking. The inclusion criteria consisted of national journal and international journal articles published between 2020 and 2025, focusing on mathematics learning contexts and discussing the relationship between controversial issues and higher-order thinking skills. A total of twenty relevant articles were selected and analyzed thematically to identify patterns related to controversial mathematical problems, reasoning processes, and critical thinking development. The results indicate that the integration of controversial issues in mathematics learning can stimulate constructive cognitive conflict, argumentative discussion, and reflective thinking, which contribute to the improvement of students’ mathematical reasoning and critical thinking skills. Topics such as conceptual misconceptions, contextual mathematical problems, and socio-scientific issues encourage students to analyze information, evaluate arguments, and construct logical solutions. In addition, several studies highlight the important role of teachers in designing and facilitating controversial problem-based learning to optimize these cognitive processes. Overall, controversial issues provide an effective pedagogical approach for fostering reasoning, analytical thinking, and reflective judgment as essential competencies in 21st-century mathematics education. Keywords: Controversial Issues, Mathematical Reasoning, Critical Thinking.